Yeah! - Bagge, Peter 1957- (Fantagraphics, 2011)
The all-girl band Yeah!--consisting of Krazy, Honey, and WooWoo--have achieved intergalactic stardom on every planet except Earth, where they struggle to achieve fame in suburban New Jersey
Previously published by DC Comics as a series of nine comic books in 1999 and 2000
Keywords: Bagge, Peter -- 1957-; Rock groups -- Comic books, strips, etc; Women rock musicians -- Comic books, strips, etc; Comic